Mechanically and biologically skin-like elastomers for bio-integrated electronics - Shuo Chen (Nature Portfolio, 2020)
Designing biodegradable and biocompatible polymers to mimic both mechanical and biological properties of skins for emerging electronic devices remains a challenge. Here, the authors propose PSeD-U skin-like elastomers with both mechanical and biological properties for bio-integrated electronics.